1981
DOI: 10.1021/jm00142a024
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of ureido and vinylureidopenicillins as inhibitors of intraruminal lactic acid production

Abstract: A series of 14 vinylureidopenicillins and a series of 9 ureidopenicillins were prepared by reaction of 6-aminopenicillanic acid with vinyl isocyanates and isocyanates. These compounds were evaluated for their potential to protect ruminants against lactic acidosis. The compounds were tested for inhibition of in vitro ruminal lactic and propionic acid production, and six compounds inhibited lactic acid production to less than 10% of control at doses of 0.31 microgram/mL or lower, whereas they did not inhibit pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In conclusion, we have demonstrated that acylation of laidlomycin at C-26 leads to compounds with a superior profile of antibiotic activity relative to the parent compound in two in vitro rumen fer- Laidlomycin (1) Monensin (2) Laidlomycin propionate (5) Laidlomycin butyrate (6) Laidlomycin hexanoate (11) Laidlomycin octanoate (15) Laidlomycin decanoate (16) Infected controls…”
Section: Compoundmentioning
confidence: 88%
“…In conclusion, we have demonstrated that acylation of laidlomycin at C-26 leads to compounds with a superior profile of antibiotic activity relative to the parent compound in two in vitro rumen fer- Laidlomycin (1) Monensin (2) Laidlomycin propionate (5) Laidlomycin butyrate (6) Laidlomycin hexanoate (11) Laidlomycin octanoate (15) Laidlomycin decanoate (16) Infected controls…”
Section: Compoundmentioning
confidence: 88%